The Creative Cardiac BioCoherence: Art, Creativity and Health Promotion - Alves, Jacqueline Mac-Dowell Lopes (Farol, 2024)
Creative Cardiac BioCoherence is a methodology that uses cardiac coherence to unlock creative potential, aligning mind and heart. Based on studies from the HeartMath Institute, the cognitive categories of Robert and Michelle Root Bernstein, and the flow theory of Mihaly Csikszentmihalyi, it proposes breathing, meditation and biofeedback techniques to promote a state of synchrony between body and mind, facilitating creativity. By integrating art and cardiac coherence practices, the method aims to foster emotional resilience, encourage authentic self-expression, and facilitate creative innovation.